Analyzing the User Experience of Virtual Reality Storytelling with Visual and Aural Stimuli - Dumlu, Burcu Nimet; Demir, Yüksel (Springer, 2020)
Storytelling is an integral part of narratives relating to our daily events, news, personal experiences, and fantasies. While humans have long narrated their stories, the mediums they have used to do so have evolved over time through the effects of technological developments: initially, storytelling was solely oral, then written forms were added, and now, with the effects of new media, such narratives have also begun to employ photography and video. These new media tools are also undergoing their own processes of expansion and development. Today one of the most attention-getting are those using Virtual Reality (VR) technologies, a means that allows users to experience being-in-thevirtual- environments, with possibilities of becoming entirely immersed in a virtual environment. The ability to experience an environment with threedimensional features enhances the experience in sensorial ways, with simultaneous stimulation of both the user’s visual and auditory sensorial systems. The aim of this study is to gain a better understanding of what exactly the user experiences through VR storytelling. To this end we have conducted an experimental research based on an examination of the immersive experience in VR, which constructs the presence feeling. The experiment has been designed to study the effects on forty users. These participants used the HTC Vive headmounted display to experience the contents of a story called “Allumette” (designed by Penrose Studios). User behaviors were recorded and observed by the tools used to collect data from both the physical world and the virtual environment. Users’ physical movements were documented as coordinate data, while the behavioral reflections in the virtual environment were recorded as a video. Following this virtual experimentation, users were asked to answer a questionnaire that measured their responses to their VR storytelling experience. User experience was finally measured by analyzing both the behavioral outputs of the subjects and the questionnaire. “Cinemetrics” methodology was implemented to analyze the camera movements, which were considered as the user behavioral reflections in VR. The results of this study based on analyzing the behaviors and the reactions to visual and aural stimuli in the VR environment both lead to a clearer understanding of VR storytelling and uses these results to propose a design guide for VR storytelling.
Keywords: Virtual Reality; Virtual Storytelling; User Experience